Implementasi Matriks Pada Tabel Input-Output Provinsi Jawa Barat Transaksi Domestik Atas Dasar Harga Produsen - Muhamad Fuji Hakiki; Elis Ratna Wulan (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The discussion in this study focuses on input-output analysis, one of the implementations of mathematical matrices useful for analyzing interrelated economic problems among others in the economic sector. Mathematics plays an important role in solving economic problems. This is because it is necessary to understand mathematical form, such as mathematical formulas and matrices. The matrices can be used to analyze the dynamics of countries and economic systems, as well as to analyze the main components of different sectors of the economy.